2006
DOI: 10.1097/01.yic.0000224790.98534.11
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil and mental health: the role of n-3 long-chain polyunsaturated fatty acids in cognitive development and neurological disorders

Abstract: Epidemiological and experimental studies have indicated that consumption of more n-3 long-chain polyunsaturated fatty acids may reduce the risk for a variety of diseases, including cardiovascular, neurological and immunological disorders, diabetes and cancer. This article focuses on the role of marine n-3 long-chain polyunsaturated fatty acids in brain functions, including the development of the central nervous system and neurological disorders. An overview of the major animal studies and clinical trials is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 178 publications
0
63
1
Order By: Relevance
“…Prominent studies in traumatic brain injury indicated a similar neuroprotective potential. Omega-3 PUFAs also possess neurotrophic properties [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Prominent studies in traumatic brain injury indicated a similar neuroprotective potential. Omega-3 PUFAs also possess neurotrophic properties [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that brain lipid metabolism may influence the development of several neurological diseases, including AD, includes the observations that (i) the gene encoding the cholesterol transporter apolipoprotein E type 4 is a major risk factor for both sporadic and familial AD, (ii) epidemiological (BarbergerGateau et al, 2002;Conquer et al, 2000;Larrieu et al, 2004;Morris et al, 2003;Tully et al, 2003;Young and Conquer, 2005) and experimental studies have indicated that increased 3 fatty acid consumption decreases the risk of developing a number of diseases including AD (reviewed in Assisi et al, 2006) and (iii) the modern human diet is deficient in 3 fatty acids compared to the paleolithic diet on which humans evolved (Broadhurst et al, 2002;Muskiet et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Changes in brain DHA are positively associated with changes in cognitive and behavioral performance [1,2]. Animal and human studies have shown that n-3 PUFA deficiency reduces DHA concentration in brain, alters neurogenesis [3] and is associated with poorer development of visual acuity and lower indices of neural development [1,2], as well as with a variety of central nervous system disorders, including Alzheimer's disease and psychiatric illnesses, such as schizophrenia and depression and mood disorders [4].…”
Section: Introductionmentioning
confidence: 99%